Atypical employment in Europe 1996-2011 - Jutta Allmendinger; Lena Hipp; Stefan Stuth (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
To assess the influence of nonstandard employment for the labor market participation of different demographic groups, we provide detailed descriptions of the development of atypical employment in comparison to standard employment, unemployment, and economic inactivity between 1996 and 2011. In our analyses, we distinguish between fixedterm employment, solo self-employment, substantial part-time work (between 20 and 35 hours/week), and marginal part-time work (less than 20 hours/week). By simultaneously considering standard employment, atypical employment, and non-employment, we are able to assess the consequences of flexible labor markets for the economic integration of different population groups, such as women, the elderly, young people, or the low-skilled.
Keywords: J21; J23; J82; 300; Labor Market; Nonstandard Employment; Atypical Employment; Part-time; Temporary Jobs; Solo self-employment; International Comparison; Europe